Naturalistic planting design : the essential guide - Dunnett, Nigel ([Bath] : Filbert Press, 2019)
Nigel Dunnetts gardens and landscapes have lifted the spirits of city dwellers for decades. They are beautiful, uplifting places that resonate with the energy of the natural world and stop us in our tracks. But how does he achieve these plantings with their successional waves of colorful perennials, elegant grasses, and pollinators at work with so few demands on irrigation and other natural resources? In this book he shares his inspiration, philosophy and working methods. He puts his own particular style of naturalistic planting in historical context, teaches us how to read wild plant communities and understand how they behave in garden situations. Finally he shares his plant selection, which includes trees and shrubs as well as perennial and annual meadow plants, and implementation techniques in a neat planting design toolkit. --Publisher
Foreword by Piet Outdolf -- Introduction: planting for people -- From the beginning -- Understanding contemporary naturalism -- Reading nature -- Planting design toolkit -- Future nature -- Cultivation Guidelines -- Epilogue.
Imported from: zcat.oclc.org:210/OLUCWorldCat (Do not remove)
boek
Keywords: Landscape gardening; Horticulture